Question

    Find the LCM of x2 - 3x + 2 and

    x2 - 5x + 6
    A (x - 2) (x + 1) (x - 1) (x - 3) Correct Answer Incorrect Answer
    B (x - 2) Correct Answer Incorrect Answer
    C (x - 2) (x - 1) (x - 3) Correct Answer Incorrect Answer
    D (x - 3) Correct Answer Incorrect Answer

    Solution

    x2 - 3x + 2 = x2 - x - 2x + 2 = x (x - 1) - 2(x - 1) = (x - 2) (x - 1)x2 - 5x + 6 = x2 - 3x - 2x + 6 = x (x - 3) - 2(x - 3) = (x - 2) (x - 3) So, required LCM = (x - 2) (x - 1) (x - 3)

    Practice Next